Nigerian economy and society : economic policy and development, 1988-89 - Phillips, Adedotun O.; Ajakaiye, David Olusanya Ishola; Nigerian Institute of Social and Economic Research (Ibadan : Nigerian Institute of Social and Economic Research, 1991)
Development in the Nigerian Economy during 1988 and 1989 largely reflect the resolute Federal Government to the structural adjustment programme (SAP), but with increased sensitivity to the consequential problems and difficulties confronting various segment of the society.
Includes bibliographical references.
uaa 24/01/19, ijb 06/02/2019
Loans.
Keywords: Nigeria; Nigeria; Nigeria; Nigeria